PENGARUH PEMBERIAN KOMPOS KULIT DURIAN PADA TYPIC HYDRAQUENT, UMBRIK DYSTRUDEPT, DAN TYPIC KANDIUDULT TERHADAP BEBERAPA ASPEK KESUBURAN TANAH (pH, C ORGANIK, DAN N TOTAL) SERTA PRODUKSI TANAMAN JAGUNG (Zea mays L.) - Rian Hardiansyah Manurung; Lahuddin Musa; Fauzi Fauzi (Universitas Sumatera Utara, 2014)
The objective of this research is to know the influencing of the Husk-pulp compost of Duriozibethinus to Typic Hydraquent, Umbrik Dystrudept, dan Typic Kandiudult on some the soilfertility aspect (pH, C organic, and N total) and the maize production. The experiment wasconducted at the green house, at Laboratory of Chemistry and Soil Fertility, and Research andTechnology Laboratory, Faculty of Agriculture, University of Sumatera Utara, Medan. Groun planof experiment was maked agree with Randomized Block Design (RBD) with 2 factors and 3replications, namely durio husk-pulp compost consist which of 5 levels: D0 (0 g), D1 (109,5 g), D2(219 g), D3 (328,5 g), D4 (438 g) and soil’s ordos, which consist of 3 levels, that are: T1 (TypicHydraquent), T2 (Umbrik Dystrudept), dan T3 (Typic Kandiudult), and 3 replications to meet 45experimental units.The results of this research showed that the increasing bend of Typic Hydraquentwas been the highest of them because of the increasing of the durio husk-pulp compost’s doses, theincreasing bend of Typic Hydraquent, Umbrik Dystrudept, and Typic Kandiudult’s C organic werebeen same relativy because of the increasing of the durio husk-pulp compost’s doses, the increasingbend of Umbrik Dystrudept and Typic Kandiudult’s N total were been same relativy because of theincreasing of the durio husk-pulp compost’s doses, except to the increasing bend of TypicHydraquent’s N total, and maize dry-weights in Typic Hydraquent, Umbrik Dystrudept, and TypicKandiudult are several increase until the same doses.